2013
DOI: 10.1111/jgh.12278
|View full text |Cite
|
Sign up to set email alerts
|

Variants in CCK and CCKAR genes to susceptibility to biliary tract cancers and stones: A population‐based study in Shanghai, China

Abstract: Background and Aim Altered motility of the gallbladder is associated with an increased risk of gallstones and can result in biliary tract cancers. Cholecystokinin (CCK) is an important modulator of gallbladder motility which functions by activating CCK type-A receptor (CCKAR). The aim of this study was to determine whether genetic variants in CCK and CCKAR are associated with the risk of biliary tract cancers and stones. Methods We investigated the associations between 9 single nucleotide polymorphisms (SNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Our study first described the upregulation of KNG1 and CCKAR in prostate cancer. Previous studies have described the presence of KNG1 and CCKAR as biomarkers of various types of cancer, such as thyroid cancer [36,37], liver cancer [38], ovarian cancer [39], and cholangiocarcinoma [40]. In different stages of PCa development and progression, especially in the process of hormone-sensitive PCa progressing to castration-resistant PCa, the proteomic alterations and transcriptomic data have significant differences in changes [41].…”
Section: Discussionmentioning
confidence: 99%
“…Our study first described the upregulation of KNG1 and CCKAR in prostate cancer. Previous studies have described the presence of KNG1 and CCKAR as biomarkers of various types of cancer, such as thyroid cancer [36,37], liver cancer [38], ovarian cancer [39], and cholangiocarcinoma [40]. In different stages of PCa development and progression, especially in the process of hormone-sensitive PCa progressing to castration-resistant PCa, the proteomic alterations and transcriptomic data have significant differences in changes [41].…”
Section: Discussionmentioning
confidence: 99%
“…The gallstone connection has largely been recognized in highly unusual kindreds, in which this receptor was found to be misprocessed and defective (32). Of note, the vast majority of patients with gallstones, including those with cholesterol gallstones, have normal CCK1R and CCK (33,50).…”
mentioning
confidence: 99%
“…Cholecystokinin A receptor (CCKAR) is a G protein-coupled receptor that can be activated by cholecystokinin (CCK), whose mutation can affect the risk of gallbladder cancer in women. 27 Previous studies have found that the expression level of CCKAR in a gallbladder with gallstones was significantly lower than that in a gallbladder without gallstones. 28 In addition, CCKAR has been found to be associated with tumor suppression and is used as a candidate gene for studying ESCC.…”
Section: Discussionmentioning
confidence: 93%